Study on Decoupling Relationship Between Carbon Emissions of Agricultural Water Consumption and Agricultural Economic Growth in Hangzhou and Its Driving Factors - ZHANG Qing; ZHU Hua; WANG Yan; XU Rouyi; CHEN Jiexun; YE Jinyang (Renmin Zhujiang)
Understanding the relationship between carbon emissions of agricultural water consumption and agricultural economic growth is of great significance for the efficient utilization of water and energy resources in agriculture and the development of the regional low-carbon economy.Agricultural-related statistical data in Hangzhou from 2010 to 2021 are utilized to calculate the carbon emissions of agricultural water consumption.The decoupling relationship between carbon emissions of agricultural water consumption and agricultural economic growth in Hangzhou is explored.The results show that:①From 2010 to 2021,the carbon emissions of agricultural water consumption in Hangzhou show a non-stationary decline trend,and the intensity of carbon emissions shows a continuous decrease trend,with reductions of 0.82×108 kg and 1.14 t/104 yuan (the Chinese currency),respectively.The temporal evolution of carbon emissions of agricultural water consumption can be roughly divided into three stages:“decrease firstly and then increase,decline with fluctuation,and relatively stable”;②The decoupling relationship between carbon emissions of agricultural water consumption and economic growth in planting industry in Hangzhou from 2011 to 2021 is mainly characterized by strong decoupling,accounting for 72.73%;③Technological effects and economic effects are the main factors promoting and inhibiting the decoupling between carbon emissions of agricultural water consumption and economic growth.